ANATOMY AND PHYSIOLOGY PERFORMANCE AS A PREDICTOR OF BASIC NURSING SKILLS COMPETENCY AMONG UNDERGRADUATE NURSING STUDENTS - Nurhayati Siagian; Evelyn Hemme Tambunan (Pena Cendekia Insani, 2026)
Anatomy and Physiology (A&P) is considered the bioscientific foundation of nursing practice, yet evidence linking A&P academic performance to objectively measured clinical skill competency remains limited, particularly within Indonesian undergraduate nursing programmers. This study examined the association between A&P academic performance and basic nursing skills competency among undergraduate nursing students in Indonesia. A retrospective correlational design was employed using administrative records from 178 Bachelor of Science in Nursing (BSN) students at Universitas Advent Indonesia, Bandung. A&P performance was operationalized as course grade (4.0 scale) and examination score (0–100%). Basic nursing skills competency was assessed via a standardized 10-station Objective Structured Clinical Examination (OSCE). Pearson product-moment correlations and simultaneous-entry multiple linear regression were used for analysis. Both A&P indicators showed moderate, statistically significant positive correlations with OSCE performance (course grade: r = 0.44; examination score: r = 0.47; both p < 0.001). The regression model was statistically significant [F(3,174) = 18.32,p < 0.001;R2 = 0.24, adjusted R2 = 0.23]. A&P course grade (beta = 0.38,p < 0.001) and examination score (beta= 0.31,p = 0.001) were independent predictors of OSCE performance, whereas overall GPA was not a unique predictor after controlling for A&P indicators (beta = 0.12,p = 0.182)